2021
DOI: 10.3389/fmicb.2020.599882
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Genetic Determinants Encoding Cadmium, Arsenic, and Benzalkonium Chloride Resistance in Listeria monocytogenes of Human, Food, and Environmental Origin

Abstract: Environmental adaptation of Listeria monocytogenes is a complex process involving various mechanisms that can contribute to their survival in the environment, further spreading throughout the food chain and the development of listeriosis. The aim of this study was to analyze whole-genome sequencing data in a set of 270 strains of L. monocytogenes derived from human listeriosis cases and food and environmental sources in order to compare the prevalence and type of genetic determinants encoding cadmium, arsenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…According to several authors, the other remaining CCs detected in this study were previously isolated from different sources, such as food and environments [10,45,46,48,[52][53][54][55][56][57].…”
Section: Distribution Of Ccs and Cg-mlst Clusters And Their Virulence And Stress Resistance Profilesmentioning
confidence: 72%
“…According to several authors, the other remaining CCs detected in this study were previously isolated from different sources, such as food and environments [10,45,46,48,[52][53][54][55][56][57].…”
Section: Distribution Of Ccs and Cg-mlst Clusters And Their Virulence And Stress Resistance Profilesmentioning
confidence: 72%
“…Heavy metals such as cadmium can be used in various pesticide products (including sanitizers) and therefore are commonly found in soils, and agricultural environments. Bacterial populations within these environments, such as L. monocytogenes, often possess genetic elements to combat this stressor [47,48]. These genes are commonly found on mobile genetic elements, such as plasmids (e.g., pLM80) or transposons (e.g., Tn5422), and their proximity in coding regions to QAC tolerance determinants (e.g., bcrABC) has led to speculation that the two may be associated.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of cad did not seem to impact QAC tolerance. In evaluating isolates from food products, clinical cases, and environmental samples for QAC and heavy metal resistance genes, Gelbicova, et al [48] found that cadmium resistance determinants were more frequently found across the samples compared to QAC tolerance genes (27.8% vs. 7%). While the prevalence rate of cadmium resistance and QAC tolerance genes was similar in the present sample set, the combination of both gene types was not found in any one isolate (i.e., isolates with bcrABC did not have either cadA1 or cadA2).…”
Section: Discussionmentioning
confidence: 99%
“…LGI2 and LGI2-like islands appear to be uncommon in L. monocytogenes serotypes other than 4b, and arsenic resistance in serotypes 1/2a and 1/2c is frequently mediated by Tn554 [21,24]. Even more surprisingly, LGI2 and its variants have until now appeared to be restricted to L. monocytogenes.…”
Section: Introductionmentioning
confidence: 99%
“…LGI2 was originally identified in serotype 4b CC2 strain Scott A and harbors a cadmium resistance cassette (cadA4C4) that conferred resistance to lower levels of cadmium (35 µg/mL) in comparison to other cadAC cassettes (70 µg/mL) [21][22][23]. Further studies revealed that LGI2 was harbored by diverse strains of L. monocytogenes, with a predilection for the serotype 4b hypervirulent clones CC1 and CC2 [9,21,24].…”
Section: Introductionmentioning
confidence: 99%